Perubahan Perilaku Anak Prasekolah dalam Pemenuhan Asupan Gizi Seimbang melalui Penerapan PAUD Sadar Gizi di TK-IT Mutiara Hati Kota Semarang - Reni Pawestuti Ambari; Lita Latiana Lita; Khamidun Khamidun Khamidun (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2018)
The purpose of this study was to examine differences of preschool children's behaviour in fulfilment balanced nutritional intake through the program of "PAUD Aware of Nutrition". Quasi experimental research methods, with the design of pre and post-test without control. The intervention was carried out by giving information by researchers to preschool children aged 5-6 years about 10 messages of balanced nutrition. Children are accompanied for one month with a frequency of once a week. The study population was preschool children who were in the Mutiara Hati Kindergarten, Semarang City. Sample collection through purposive random sampling, a total of 38 children. Pre and post are one month apart. The Paired T-Test Sample Test results showed that there were differences (p <0.05) in children's behaviour between before and after the program of "PAUD Aware of Nutrition" intervention. Recommendations from this study are the need for the implementation of the Nutrition Awareness PAUD program in PAUD institutions for healthy living habits and prevention of nutritional problems in preschool children. Keywords: PAUD Aware of Nutrition, 10 Messages of Balanced Nutrition, Behaviour, and Preschool Children. AbstrakTujuan penelitian ini adalah mengetahui perbedaan perilaku anak prasekolah dalam pemenuhan asupan gizi seimbang melalui penerapan “PAUD Sadar Gizi”. Metode penelitian dengan quasi eksperimental, dengan desain pre dan posttest without control. Intervensi yang dilakukan adalah pemberian informasi oleh peneliti kepada anak prasekolah usia 5-6 tahun tentang 10 pesan gizi seimbang. Anak didampingi selama satu bulan dengan frekuensi satu minggu sekali. Populasi penelitian yaitu anak prasekolah yang berada di TK IT Mutiara Hati, Kota Semarang. Pengumpulan sampel melalui purposive random sampling, sejumlah 38 anak. Pre dan post berjarak satu bulan. Hasil Uji Paired Sampel T-Test didapatkan ada perbedaan (p<0,05) perilaku anak antara sebelum dan sesudah intervensi PAUD Sadar Gizi. Peningkatan  Rekomendasi dari penelitian ini adalah perlunya pelaksanaan program PAUD Sadar Gizi di lembaga PAUD untuk pembiasaan hidup sehat dan penanggulangan masalah gizi pada anak usia prasekolah.Kata Kunci: PAUD sadar gizi, 10 pesan gizi seimbang, perilaku, anak prasekolah.